Pesantren dan Perguruan Tinggi Agama Islam Menghadapi Liberalisasi Pendidikan - Ainnurrafiq Dawam (Universitas Islam Indonesia, 2006)
Since 1994, liberation of education has been rolled in Indonesia. Government of Indonesia has been ratified liberation of education with UU No. 47, 1994. Indonesia has to implement it on all guide lines of national education. Free from positive or negative effect, Indonesian government and citizen have to realize the significant and the urgent of liberation of education. Part of institution of education in Indonesia are Pesantren and PTAI (Islamic university). This article would like to discuss shortly about readiness of pesantren and PTAI (Islamic university) to commemorate liberation of education.